Β-Galactosidase from Exiguobacterium Acetylicum: Cloning, Expression, Purification and Characterization - Vasquez-Guzman, C; Arenas-Salinas, F; Vera-Vera, C; Cornejo-Leiva, F; Castillo-Astudillo, C (Elsevier Ltd, 2019)
The main goal of this work was to evaluate the performance of β-galactosidase from Exiguobacterium acetylicum MF03 in both hydrolysis and transgalactosylation reactions from different substrates. The enzyme gene was expressed in Escherichia coli BL21 (DE3), sequenced, and subjected to bioinformatic and kinetic assessment. Results showed that the enzyme was able to hydrolyze lactulose and o-nitrophenyl-β-D-galactopyranoside, but unable to hydrolyze lactose, o-nitrophenyl-β-D-glucopyranoside, butyl- and pentyl-β-D-galactosides. This unique and novel substrate specificity converts the E. acetylicum MF03 β-galactosidase into an ideal catalyst for the formulation of an enzymatic kit for lactulose quantification in thermally processed milk. This is because costly steps to eliminate glucose (resulting from hydrolysis of lactose when a customary β-galactosidase is used) can be avoided. © 2019 Elsevier Ltd